The Republican Governement merchant marine and the maritime traffic from the USSR: Supplies and weapons for the Spanish War - García Santamaría, José Vicente; Sánchez Illán, Juan Carlos (Hispania Nova, 2023)
The importance of the Spanish merchant navy in the course of the Spanish civil war is beyond any doubt. According to our estimation, the fleet that the Republic government came to control accounted for slightly more than 20 per cent of the existing tonnage in Spain at the beginning of the war. Although in qualitative terms, and in terms of the number of modern motor ships, its represented more than a third of the total. To the deployment of this fleet, we must add the fleet of the Basque Government, and, naturally all the foreign ships that supplied the Republic with weapons, in addition to France Navigation Company. That is, sufficient logistics to send supplies to the territory controlled by the Republic. Based on the handling of these figures, our objective in to unravel the keys by means this merchant fleet came to suffer a serious collapse from the second half of 1937 and an almost total stoppage at the end of the following year. The reason for this fatal outcome should be attributed to the control of the Mediterranean that the rebel navy came to exercise in short time, as well as the lack of operability of the Republican Navy.
Keywords: Spanish Civil War; Spanish Civil War at sea; republican fleet; merchant traffic Spanish Civil War; civil war navy